張嘉璈的信託觀 - 許海波 (國際人文社科研究, 2025)
Zhang Jia'ao (1889-1979), was from Baoshan, Jiangsu Province (now part of Shanghai). He was a renowned banker during the Republic of China era. He held positions such as the deputy manager of the Shanghai Branch of the Bank of China, vice president of the Bank of China, and later vice president of the Central Bank. He was also entrusted with the task of preparing the Central Trust Bureau and served as its first director. During the War of Resistance against Japanese Aggression and after the war, Zhang Jia'ao successively held positions such as Minister of Railways, Minister of Communications, Director of the Economic Committee of the Northeastern Command, and President of the Central Bank of the Nanjing National Government. He later settled abroad and passed away there. Zhang Jia'ao's main focus was on national currency systems and the modernization of banks. He was also directly involved in the governance and supervision of some trust companies, but there is little historical record about his attitude towards trusts. In his later work, "The Inflation Spiral: Ten Years of the Total Collapse of China's Monetary Economy," Zhang Jia'ao rarely mentioned the trust system and the trust industry. Zhang Jia'ao's view on trust was not clear. This article discusses it based on historical facts.